Kuzeydoğu Akdeniz Bölgesinde Yaşayan Adi Köpekbalığı, Mustelus mustelus (Linnaeus, 1758)’un Mide İçeriği - Özcan, Ebru İfakat; Başusta, Nuri (Fırat University, 2016)
Bu çalışmada; Kuzeydoğu Akdeniz bölgesinde yaşayan Mustelus mustelus (Linnaeus, 1758) bireylerinin mevsimsel beslenme rejimi belirlemek için mide içerikleri incelenmiştir. Bu amaçla total boyları 149-44,3 cm; ağırlıkları 8776-247,6 g arasında değişim gösteren ve Nisan 2012-Nisan 2014 tarihleri arasında avlanan 123 M. mustelus Değerlendirmelerde, mevsimlere göre tespit edilen besin gruplarının sayısal varlık, bulunuş frekansı ve nispi önemlilik indeksleri (% IRI) hesaplanmıştır. Sonuç olarak, Kuzeydoğu Akdeniz bölgesinde yaşayan M. mustelus bireylerinde krustasealar ile balıklar en önemli av grupları olup (sırasıyla %IRI = 61,1 ve %IRI =28,7) olarak bulunmuşlardır. Sefalapodlar ikincil av grubunu (%IRI =8,5) oluşturmuşlardır. Poliketler (%IRI =1,7) ise nadir av grubudur.

In this study, stomach contents of Mustelus mustelus (Linnaeus, 1758) obtained from the Northeastern Mediterranean were examined to determine seasonal diet regime. For this purpose, 123 of M. mustelus with 44.3-149.0 cm in total length and 247.6-8776 g in weight that were caught between April 2012-2014 for examination. 120 of them (97.5%) were found to be the full of the stomach. In evaluation, numerical presence, frequency of occurrence and relative importance index (% IRI) food groups according to the seasons were calculated. In conclusion, the most important food groups for M. mustelus living in the Northeastern Mediterranean were Crustaceans and fish (with IRI= 61.1% and IRI = 28.7% respectively). Second group was Cephalopods with IRI = 8.5 %. Polychaeta (IRI = 1.7 %) was the rare in the food groups
Digestive System Contents of the Mustelus mustelus (Linnaeus, 1758) Inhabiting Northeastern Mediterranean